APLIKASI INSENTIF BERBASIS WEB PADA PT. ST MORITA INDUSTRIES - Farista Aprillia; Reza Pratama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The purpose of writing this Final Project analysis is to develop a web-based program especially for sales incentive applications, using PHP Hypertext Preprocessor PHP which is useful in managing data at PT. ST Morita Industries. In this case the author wants to make the sales incentive program easier and accessible to users. The method used in collecting the data and information needed which includes data by conducting interviews, literature studies, analytical methods by conducting ongoing surveys, and waterfall iterative methods. The results and analysis of this application are expected to provide results that are efficient, fast and precise. The writings that I can take are by analyzing and analyzing incentive sales, so that it can improve the quality and efficiency of sales and be done easily and quickly.